Potential of palm oil fuel ash as a partial replacement of fine aggregates for improved fresh and hardened mortar performance - Zaimi, Siti Adriana; Muhd Sidek, Muhd Norhasri; Hashim, Nor Hafida; Mohd Saman, Hamidah; Putra Jaya, Ramadhansyah; Marzuki, Nur Ashikin (Hindawi, 2023)
The growth of Malaysia has caused many industries to grow rapidly, especially construction industries due to the demand for more homes, buildings, and infrastructure. The production of concrete and mortar is highly requested. Therefore, the demand for fine aggregate becomes higher because fine aggregate is one of the main elements in concrete and mortar production. The high demand for fine aggregates will create a worrying situation where the fine aggregate crisis will worsen. An alternative was introduced to replace the fine aggregate known as palm oil fuel ash (POFA) in order to reduce the use of natural resources such as fine aggregates and lead to the reduction of fine aggregate mining activity. POFA produced from palm oil fibre, palm oil shell, and mesocarp at high temperature has no benefits in the commercial return. Thus, POFA that has accumulated in landfill has the ability to create environmental pollution. Due to the pozzolanic behaviour of POFA, it could be relevant when POFA is used in the production of mortar as a partially fine aggregate replacement. There is a limited study on the effects of POFA as a partially fine aggregate replacement in the production of mortar. The aim of this research is to study the effects of POFA on the workability of fresh mortar, and for the hardened mortar, compressive strength and microstructural analysis will be analysed. A total of 45 cubes with dimensions of 100 mm × 100 mm × 100 mm were cast at different percentages of POFA at 0%, 2.5%, 5%, 7.5%, and 10% by the weight of fine aggregates. Slump and flow table tests were conducted during the casting process to determine the workability. All the specimens were water cured at days 3, 7, and 28 before being tested with a compression test and scanning electron microscope (SEM) on the hardened mortar. It was discovered that 0% POFA recorded the highest workability. Furthermore, the laboratory results showed that the 2.5% POFA in the mortar recorded the highest compressive strength compared to other specimens. Moreover, the microstructure of the mortar specimen was observed to be denser, and the pores were refined with the presence of POFA, compared to the control specimen. Based on the findings, this research enables us to give an understanding of the effect of POFA incorporated in mortar as a partially fine aggregate replacement in terms of workability, compressive strength, and microstructural analysis. Based on the results from this research, the advantage of POFA can be fully utilized and can help reduce the environmental problems.